Can Prescription Drug Use Disorder Predict Suicidality in US Adults With Chronic Pain? A Pilot Study Based on Collaborative Psychiatric Epidemiological Surveys. Issue 6 (December 2020) - Abdelghani, Mohamed; Ibrahim, Shimaa; Said, Amira; Foad, Eman
Abstract : Background: Individuals with chronic pain are at higher risk for suicide than other populations, and their potential for prescription drug use disorder (PDUD) enormously exists. This study aimed to estimate the prevalence and correlates of suicidality and to determine its relation to PDUD, among US adults with a history of chronic pain. Methods: Data were obtained from the Collaborative Psychiatric Epidemiology Surveys (2001–2003). This analysis was limited to respondents who had a history of chronic pain (N = 5301). Logistic regression was used to determine the association between suicidality and prescription drug use disorder among those populations. Results: Among study respondents, there was a strong positive association between PDUD and suicidal ideation and attempts ( P value < 0.001, = 0.006, respectively). Adjusted logistic regression analysis showed those with PDUD had 1.5 times greater likelihood of suicidal ideation (95% CI 1.2–1.8). Among respondents with a history of chronic pain and PDUD, Non-Hispanic Whites, female gender, lifetime mood and/or anxiety, and substance use disorders were associated with increased suicide risk ( P value = 0.020, = 0.011, < 0.001, < 0.001, respectively). Conclusions: There is a robust relationship between PDUD and suicidality in US adults with a history of chronic pain. Ethnicity, gender, and comorbid mood, anxiety or substance use disorders can predict suicidality among individuals with both chronic pain and PDUD. Longitudinal studies need to investigate the causal relationship between PDUD and suicidality among those populations.